The relationship between forest research and forest management in China: an analysis of four leading forestry journals - Ruíz Pérez, M.; Fu Maoyi; Xie Jinzhong; Yang Xiaosheng; Belcher, B. (2004)
This article analyses the collaboration between forestry research institutions and forestry departments in China based on a bibliometric study of four leading Chinese forestry journals. Multiple-authored papers are frequent, and there is a significant collaboration between research and implementing agencies. This collaboration centres on applied research, being less common on fundamental research and almost non-existent on policy research. Universities, National research institutes and National and Provincial level forest departments act as the key organisers of research, with specialised domains and types of collaboration. This helps explain the success of Chinese forestry experiences in recent years.